Bone health in childhood and adolescence: an overview on dual-energy X-ray absorptiometry scanning, fracture surveillance and bisphosphonate therapy for low-middle-income countries - Madhuchani, Dilki; Seneviratne, Sumudu Nimali; Ward, Leanne M. (Frontiers in Endocrinology, 2023)
Bone health in childhood determines bone health in later life. Loss of bone strength during early life also leads to increased morbidity and reduced quality of life in childhood and adolescence. Bone health can be evaluated by dual energy x-ray absorptiometry. Bone mineral density Z-scores and bone mineral content are surrogate measures of bone strength in growing individuals. Indications for DXA in childhood include evaluation of clinically significant fractures, diagnosis of primary and secondary bone fragility disorders and monitoring of children at risk for compromised bone strength. However, obtaining DXA images can be challenging, especially in younger children, due to difficulty in positioning and movement artefacts. Furthermore, paediatric DXA interpretation is complicated by effects of growth and puberty. Bisphosphonates are the mainstay of treatment for childhood bone fragility disorders. Other supportive measures to improve bone strength include optimizing nutrition, encouraging weight bearing physical activity within the limits of the underlying condition, and treating any associated endocrinopathies. With increased availability of DXA facilities and bisphosphonates in LMIC, there is now greater opportunity for improving the diagnosis and management of children and adolescences with primary and secondary bone fragility disorders. However, there is still lack of awareness on utilizing these resources optimally to optimize bone health among childhood and adolescents. We provide an evidence-based approach to the assessment and management of childhood bone disorders suitable for LMIC settings.